Buchwald‐Hartwig amination reaction of aryl halides using heterogeneous catalyst based on Pd nanoparticles decorated on chitosan functionalized graphene oxide. (13th June 2017) - Sarvestani, Mosayeb; Azadi, Roya
Abstract : In this work, graphene oxide was functionalized with chitosan (GO‐Chit) followed by a simple approach for immobilization of palladium nanoparticles onto a chitosan grafted graphene oxide surface. The Pd‐nanocomposite (GO‐Chit‐Pd) was characterized using Transmission Electron Microscopy (TEM), Fourier transforms infrared spectroscopy (FT‐IR), and X‐ray diffraction (XRD) measurements. The catalytic activity of the prepared heterogeneous graphene oxide functionalized chitosan‐palladium (GO‐Chit‐Pd) was investigated in term of C‐N coupling reaction (Buchwald‐Hartwig amination reaction of aryl halides) yielding products of N‐arylamines. The easy purification, convenient operation, and environmental friendliness, combined with a high yield, render this method viable for use in both laboratory research and larger industrial scales. Studying the reusability of the catalyst in this work showed that it could be reused for five times without obvious loss in catalytic activity. Abstract : Graphene oxide was functionalized with chitosan (GO‐Chit) followed by a simple approach for immobilization of palladium nanoparticles onto a chitosan grafted graphene oxide surface. The catalytic activity of the prepared heterogeneous graphene oxide functionalized chitosan‐palladium (GO‐Chit‐Pd) was investigated in term of C‐N coupling reaction (Buchwald‐Hartwig amination reaction of aryl halides) yielding products of N‐arylamines.